Paths to carbon neutrality in china’s chemical industry - Li, Yan; Mei, Yueru; Zhang, Tao; Xie, Yuanbo (Frontiers in Environmental Science, 2022)
Chemical industry is an important pillar industry of China's economy with high energy consumption and carbon emissions. In the context of “peaking carbon emissions and carbon neutrality” target in China, it is imperative for the chemical industry to reduce carbon emissions. Based on literature on carbon emission reduction path and the analysis of the development status of chemical industry, this paper identifies the opportunities and challenges of carbon emission reduction in the chemical industry and proposes several feasible paths for China's chemical industry to achieve carbon neutrality.